The Relationship Between Situational Leadership Style and Motivation with Employee Performance at Kamonji Community Health Center in West Palu District, Palu City - Napirah, Muhammad Ryman; Vidyanto, Vidyanto; Prayitno, Heru Kukuh; Hasanah, Hasanah; Sari, Nur Mila; Fadjriah, Rasyika Nurul (Media Publikasi Cendekia Indonesia, 2024)
In the context of self-development, leaders capable of guiding organizations towards their objectives are essential. Effective leadership requires the application of diverse leadership styles in different situations, rather than relying on a single approach for all scenarios. Employees within a company can be motivated by fulfilling their needs and desires. However, providing work motivation can be challenging as what is considered important to one individual may not be equally significant to another. The head of the Kamonji Community Health Center employs a situational leadership style. The leadership of the health center head demonstrates limited communication and control, with interactions primarily occurring when employees submit reports to the head. This study aims to investigate the relationship between situational leadership style and motivation with employee performance at the Kamonji Community Health Center in West Palu District, Palu City. The research design employed is a cross-sectional study. The population comprises employees with civil servant status, with a sample size of 54 individuals selected using total sampling technique. Data analysis was conducted descriptively, including univariate and bivariate analyses, at a 95% confidence level (p<0.05). Fisher's Exact test results indicate that situational leadership style is associated with employee performance (ρ=0.039), and motivation is related to employee performance (ρ=0.028). Higher levels of situational leadership style and motivation provided correspond to improved employee performance, and vice versa. It is recommended that the head of the Community Health Center pay attention to behavioral aspects, particularly in motivating employees.